1999
DOI: 10.1074/jbc.274.46.33131
|View full text |Cite
|
Sign up to set email alerts
|

A Catalytically Active Jak2 Is Required for the Angiotensin II-dependent Activation of Fyn

Abstract: Recent work with interleukins has shown a convergence of tyrosine phosphorylation signal transduction cascades at the level of the Janus and Src families of tyrosine kinases. Here we demonstrate that activation of the seven-transmembrane AT 1 receptor by angiotensin II induces a physical association between Jak2 and Fyn, in vivo. This association requires the catalytic activity of Jak2 but not Fyn. Deletion studies indicate that the region of Jak2 that binds Fyn is located between amino acids 1 and 240. Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…RASM-control cells were created by transfecting primary RASM cells with a neomycin-resistant cassette, whereas RASM-DN cells were created by stably transfecting RASM cells with a Jak2 dominant negative mutant in order to inhibit the function of endogenously expressed Jak2. These cells have been characterized previously (14). To determine whether expression of the Jak2 dominant negative could inhibit Jak2 tyrosine phosphorylation in response to hydrogen peroxide, the two cell types were treated with 0.2, 0.5, or 1 mM hydrogen peroxide for 0, 5, or 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RASM-control cells were created by transfecting primary RASM cells with a neomycin-resistant cassette, whereas RASM-DN cells were created by stably transfecting RASM cells with a Jak2 dominant negative mutant in order to inhibit the function of endogenously expressed Jak2. These cells have been characterized previously (14). To determine whether expression of the Jak2 dominant negative could inhibit Jak2 tyrosine phosphorylation in response to hydrogen peroxide, the two cell types were treated with 0.2, 0.5, or 1 mM hydrogen peroxide for 0, 5, or 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Culture-Creation and characterization of the RASM-control and RASM-DN cells has been described previously (14). These cells were cultured in Dulbecco's modified Eagle's medium containing 4.5 g/liter glucose and 10% fetal bovine serum and growth-arrested in serum-free Dulbecco's modified Eagle's medium for 48 h prior to the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine this, a vascular smooth muscle cell line was generated which overexpressed a catalytically-inactive form of Jak2. 38 It was previously demonstrated that inhibition of the Jak2 kinase domain, either by pharmacological means or by a point mutation in the kinase domain, prevented Jak2 from binding the AT 1 -receptor. 39 Since the modified smooth muscle cell line expressed the catalytically inactive form of Jak2, Ang II treatment would not induce AT 1 /Jak2 physical co-association.…”
Section: At 1 -Receptor Signalling Mechanisms Utilising Heterotrimerimentioning
confidence: 99%
“…Using this system, it was demonstrated that STAT1 tyrosine phosphorylation was severely compromised in cells that expressed the inactive form of Jak2. 38 To determine whether the failure of STAT1 tyrosine phosphorylation resulted in the specific loss of gene transcription within the nucleus, the Ang II-dependent accumulation of c-fos mRNA was examined. Ang II induces the expression of several early growth response genes including c-fos.…”
Section: At 1 -Receptor Signalling Mechanisms Utilising Heterotrimerimentioning
confidence: 99%